Isolated testicular metastasis from prostate cancer following three years of hormone therapy and radiotherapy - Ali Tabibi; Mohammad Sajjad Zabihi; Mahyar Najarian; Mehdi Dadpour (Urology Case Reports, 2025)
This case report presents a 61-year-old male patient diagnosed with high-risk prostate cancer who underwent hormone therapy and radiotherapy. Three years after beginning treatment, rising prostate-specific antigen (PSA) levels led to a PET CT scan, which identified isolated metastases in the left testicle. The patient then underwent a radical orchiectomy. One-year follow up revealed undetectable PSA and no evidence of any metastases. The significance of this case lies in the uncommon occurrence of testicular metastasis from prostate cancer, particularly when presenting in isolation after a prolonged period following hormone therapy and radiotherapy.